UPAYA MENUMBUHKAN SELF-CONFIDENCE BERBICARA BAHASA ARAB MELALUI APLIKASI PLOTAGON PADA MAHASISWA IAIN SYEKH NURJATI CIREBON - Umamatul Bahiyah; Septi Gumiandari (CV. ADIBA AISHA AMIRA, 2024)
Efforts to increase self-confidence are a very important component in the learning process, in order to train self-confidence and mentally train students, especially to have the courage to appear in public. One ability that can be improved is the ability to speak foreign languages, especially English and Arabic. If you look at it from time to time, foreign languages such as Arabic are currently an important language to learn, just like English. This research seeks answers to the questions 1) What is the level of self-confidence in speaking Arabic of IAIN Syekh Nurjati students? efforts to grow self-confidence. This research uses descriptive qualitative methods by collecting data in the form of interviews and filling out questionnaires on research subjects. This research resulted in the finding that the majority of IAIN Syekh Nurjati students have great self-confidence and the Plotagon application to improve their Arabic speaking skills is very helpful for students, because the application has many features that can help its users.